HLA alleles modulate EBV viral load in multiple sclerosis - Simone Agostini (Journal of Translational Medicine, 2018)
Abstract Background The etiopathology of multiple sclerosis (MS) is believed to include genetic and environmental factors. Human leukocyte antigen (HLA) alleles, in particular,  are associated with disease susceptibility, whereas Epstein Barr Virus (EBV) infection has long been suspected to play a role in disease pathogenesis. The aim of the present study is to evaluate correlations between HLA alleles and EBV infection in MS. Methods HLA alleles, EBV viral load (VL) and serum anti-EBV antibody titers were evaluated in EBV-seropositive MS patients (N = 117) and age- and sex-matched healthy controls (HC; N = 89). Results Significantly higher DNA viral loads (p = 0.048) and EBNA-1 antibody titer (p = 0.0004) were seen in MS compared to HC. EBV VL was higher in HLA-B*07+ (p = 0.02) and HLA-DRB1*15+ (p = 0.02) MS patients, whereas it was lower in HLA-A*02+ (p = 0.04) subjects. EBV VL was highest in HLA-A*02−/B*07+/DRB1*15+ patients and lowest in HLA-A*A02+/B*07−/DRB1*15− individuals (p < 0.0001). HLA-B*07 resulted the most associated allele to EBV VL after multiple regression analysis considering altogether the three alleles, (p = 0.0001). No differences were observed in anti-EBV antibody titers in relationship with HLA distribution. Conclusions Host HLA-B*07 allele influence EBV VL in MS. As HLA-class I molecules present antigens to T lymphocytes and initiate immune response against viruses, these results could support a role for EBV in MS.